MR imaging-anatomical-histological evaluation of the abdominal muscles, aponeurosis, and adductor tendon insertions on the pubic symphysis: a cadaver study. Issue 118 (September 2019) - De Maeseneer, Michel; Forsyth, Ramses; Provyn, Steven; Milants, Annemieke; Lenchik, Leon; De Smet, Aron; Marcelis, Stefaan; Shahabpour, Maryam
Highlights: The adductor insertions are clarified. The adductor longus tendons cross connect. There is no thick aponeurotic connection. A thin posterior aponeurosis terminates in the midline. A thin anterior aponeurosis connects to the adductor longus tendons. Abstract: Purpose: To perform an MR(magnetic resonance) imaging, anatomical, and histological evaluation of theabdominal muscles and adductor tendon insertions. Method: Four fresh cadaveric pelvis specimens were imaged at 3 T with the following imaging parameters: TE (echo time)/TR (repetition time): 20, 4090, slice thickness: 2 mm, FOV: 270 × 90, matrix size: 512. Anatomical slices were obtained with a band saw andphotographed. MR images and photographs were evaluated by an anatomist and radiologist. Selected 3 mm thick slices were placed in formalin and decalcified, cut, placed on large slides, and stained with hematoxylin eosin stain (HES). Results: The main adductor tendon insertions are: the anterosuperior aspect of the pubic bone for the adductor longus, the anteroinferior aspect of the pubic bone - for the adductor brevis, and the inferior aspect of the pubic bone for the adductor magnus. On histology, the adductor longus tendon fibers inserted perpendicularly into the bone at a fibrocartilage enthesis and cross connected along the anterior pubic ligament into the controlateral tendon.The rectus abdominis-pyramidalis unit was covered by a thin anterior and posterior aponeurosis. The posterior aponeurosis inserted into the superior aspect of the anterior pubic ligament, whereas the anterior aponeurosis fused distally with the adductor longus tendons. Conclusion: Our findings demonstrate the insertions of the adductor tendons, on the pubic ligament and pubic bone.Histologically, the adductor longus tendon fibers inserted perpendicularly into the bone through a fibrocartilage enthesis, and cross connected along the anterior pubic ligament into the contralateral tendon.